Optimasi Prediksi Harga Saham BBNI melalui Integrasi Proses ETL dan Algoritma Long Short-Term Memory - I Gusti Ngurah Rangga Mahesa; I Wayan Sudiarsa; I Putu Dicky Dharma Suryasa; Putu Agus Aditya Putra; Yulianus Kevin Dharmawa Sagur (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Stock price prediction remains a complex challenge due to the dynamic and non-linear nature of financial markets, especially for banking stocks like PT Bank Negara Indonesia (Persero) Tbk (BBNI). This study aims to optimize BBNI stock price forecasting by integrating an automated Extract, Transform, Load (ETL) pipeline with the Long Short-Term Memory (LSTM) algorithm within a data engineering framework. Historical data from 2019 to 2025 were processed through a structured ETL sequence—including data cleaning, feature engineering, and MinMaxScaler normalization—to ensure high data quality. The dataset was partitioned into 80% for model training and 20% for testing to ensure rigorous evaluation. The results demonstrate that the systematic ETL approach significantly enhances model stability and predictive accuracy compared to conventional methods. The LSTM model effectively captured long-term temporal dependencies, providing reliable trend forecasts with an impressive test accuracy, achieving a Root Mean Squared Error (RMSE) of 0.0354. This research underscores that integrating robust data engineering practices with deep learning is essential for building resilient financial decision-support systems.